Increasing Energy Efficiency in the Manufacturing Process in Bangladesh’s Re-Rolling Mills - Mohammed, Sheikh Hasan Iqbal (World Bank, Washington, DC, 2012)
The re-rolling mill (RRM) industry, which turns scrap material into finished steel, is one of the most important suppliers to the construction industry in Bangladesh. Yet local RRM owners are unaware of, and left unaccountable for, their industry's adverse effects on the environment. This smart lesson describes the challenges and lessons learned from the International Finance Corporation (IFC) South Asia Enterprise Development Facility's (SEDF) experience in working with RRM owners in Bangladesh to demonstrate the business case for looking after social and environmental concerns.